Student Exchange Program of Merdeka Belajar-Kampus Merdeka (MBKM) in COVID-19 Pandemic - Shelly Andari; Windasari; Aditya Chandra Setiawan; Ainur Rifqi (JPP (Jurnal Pendidikan dan Pembelajaran), 2021)
The MBKM student exchange program is conducted in the Department of Educational Management, FIP, State University of Surabaya. The program is implemented online considering the pandemic is still ongoing. This research has a high urgency because it is important to know how the management of MBKM student exchanges during the Covid-19 pandemic, considering that so far student exchanges have been carried out directly or face-to-face before the Covid-19 pandemic. A qualitative approach with the case study method was used in this research. The results showed that student exchange management started from planning, organizing, implementing, to evaluating. The four steps are summarized in seven activities in the management of MBKM student exchange during the pandemic in the Department of Education Management, FIP Unesa, namely: (1) planning; (2) socialization; (3) recruitment; (4) student orientation; (5) student placement; (6) student development; and (7) recording and reporting. This study can be used as recommendations for the implementation of online student exchanges by other universities because it shows the process starting from program planning, organizing, implementing, to evaluation.